Mathematical Literacy Skills Reviewed From Mathematical Resilience in The Learning of Discovery Learning Assisted by Schoology - Afriyanti, Ice; Mulyono, Mulyono; Sri Noor Asih, Tri (Unnes Journal of Mathematics Education Research, 2018)
This study has purpose to describe the quality of learning of Discovery Learning assisted by Schoology toward the mathematical literacy skills of students of grade X SMA Negeri 1 Blora and found the patterns of mathematical literacy skills that were analyzed based on the students' mathematical resilience. This study applied mixed method type of research with embedded concurrent embedded design. The subjects of this study were the students of grade X SMA Negeri 1 Blora. The result showed that. (1) the learning of Discovery Learning assisted with Schoology toward the mathematical literacy of students is considered good qualified. (2) found the patterns mathematical literacy skills such that (1) students with high mathematical resilience were able to master the five aspects of literacy skills, and master the two other aspects very well, (2) students with moderate mathematical resilience were able to master three aspects very well, and can master the four other aspects well, (3) students with low mathematical resilience, two aspects of literacy skills can be mastered well, average on one aspect of the literacy skills, and less well in mastering the other four aspects of literacy skills.